Literature review of the research on nursing students’ professional self-concept - Yun Xu; Yongqi Liang; Hui Ye; Yue Xu (Medical Education Online, 2023)
ABSTRACTObjective To understand the current situation and progress of nursing students’ professional self-concept, this review aimed to perform a general analysis of research related to the connotation of professional self-concept, measurement tools, influencing factors, effects, and intervention experiments.Methods Three databases (Web of Science, PubMed, and CNKI) were searched for relevant articles. Research articles that met specific criteria were included, with identified articles initially screened by title and keyword. Then the abstracts were screened for relevance, and the full text was read for validation before inclusion. Descriptive analysis was performed with relevant findings from data retrieved from various sources.Results Finally, 54 articles that met the criteria were included, which organised the connotation of self-concept of nursing speciality, and introduced six measurement scales, such as Professional Self-Concept of Nurses Instrument and Nurse’s Self-Concept Questionnaire. A total of 16 investigations on influencing factors were described, and the results showed that there were internal individual and external environmental factors. The professional self-concept was formed by analysing both factors. This paper described 17 effect surveys and found that professional self-concept had an important impact on students’ mental health, academic performance, and professional values, and so on. Eight intervention experiments including attribution training and hierarchical teaching were evaluated.Conclusions Research articles on the professional self-concept included in this review were rich. These articles clarified the basic connotation of the concept, developed relatively mature measurement tools, found many influencing factors and effects, and proposed effective intervention strategies. They were of great value for understanding the professional self-concept and could provide a reference for scholars to conduct relevant research and practice. It also presents research prospects in this field, aiming to inspire future research.